Analisis Kemampuan Pemecahan Masalah Matematis Siswa Pada Materi Fungsi Komposisi - Fenti Amanda Putri; Selvia Erita (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Problem-solving is so important that it makes mathematics teaching a common goal. It is estimated that students who are capable of solving these problems can contribute to the economic growth of their country. Therefore, researchers are interested in analyzing students' ability to solve mathematical problems. Data is taken using the essay test instrument and analyzed using a descriptive quantitative approach. The subject of this study is a student of class XI SMAN 3 Sungai Penuh of 29 people. This research found that students' abilities in composition functions material were well assessed. However, in the problem-solving capabilities measured based on problem-solving indicators, there is still an obstacle to the first indicator, which is to display what is known and what is asked. But for the other three indicators, there are only a few obstacles even no obstacles at all. It is hoped that the obstacles experienced by students in this research can also be the background for further research.